RISK ANALYSIS FOR THE INFRASTRUCTURE OF A HYDROGEN ECONOMY - Rosyid, O A (185P -3466)
Increasing scarcity of fossil fuels makes the deployment of hydrogen in combination with renewable energy sources or the utilization of electricity from full time operation of existing power stations an interesting alternative. A pre-requisite is, however, the safety of the required infrastructure is investigated and its design is evaluated with the associated risk to know, at least, the risks are not higher than that of existing supplies.  Therefore, a risk analysis considering its most important objects such as storage tanks, filling stations, vehicles as well as heating and electricity supplies for residential buildings was carried out. The last is considered as representative of the entire infrastructure. The risk analysis is based on fault and event tree analyses, wherever required, and consequence calculations using the PHAST code. The procedure for evaluating the risk and corresponding results will be presented taking one of the objects as an example.